THINKING MORE DEEPLY & COLLABORATING MORE CLOSELY: HOW CO-TEACHING IS CHANGING STUDENT TEACHING - Jennette, Matthew (East Carolina University, 2021)
Read about the experiences of interns and clinical teachers participating in a co-teaching model of student teaching. Analysis of focus group data from six-years of implementation is shared. Participants will explore the positive impacts of co-teaching, lessons learned regarding implementation, and implications for teacher education.
Keywords: Co-teaching; Education